(untitled) (Research, Society and Development, 2022)
In the first half of 2020, a viral pandemic caused by SARS-CoV-2 (severe acute respiratory syndrome of coronavirus), spread exponentially through direct or in direct contact. The objective of the article is to demonstrate the necessary biosecurity standards and steps for dental care against the new virus, avoiding cross-contamination. The referring work is a literature review with a search in Pubmed, Google Scholar, Scielo, with dates from 2020 to 2022. The present result is the service performed by appointments or in cases of emergencies, in addition to reducing aerosols in the procedures when possible, it is imperative to carry out a routine disinfection of the place and sterilization of all materials used, with the use of personal protective equipment. Therefore, it is necessary to update biosafety guidelines in health services, avoiding contamination between professionals and patients.